POVERTY ALLEVIATION IN NIGERIA: AN INSIGHT INTO JAIZ BANK ISLAMIC MICROFINANCE SCHEME - Isahi, Abdullahi; Muwazir, Mohd Rizal (Online Journal of Islamic Management and Finance (OJIMF), 2024)
The purpose of this paper is to investigate Jaiz bank Islamic microfinance and poverty alleviation in Nigeria. The paper used qualitative method using exploratory techniques and interview with 15 customers respondents and 3 Jaiz bank executives carried out the research with semi-structured interviews and face-face approach to analyse on how microfinance evolved in poverty alleviation in Nigeria. Jaiz bank microfinance is systematically useful in capacity building and entrepreneurial development of active poor and enhances standard of living of underprivilege. The research goes a long way in reducing the rate of unemployment and empowering potential local communities and reducing difficulties among the poor in Particular in the Northern part of Nigeria. The paper differs from previous studies on the development of microfinance in Nigeria, in sub-Saharan African countries for which research on Islamic microfinance is sparse. The paper is unique in analysing finding and discussing on how microfinance emerged as way of poverty alleviation in the Nigerian context.